Développement d’un bioformulant à base d’huiles essentielles du zeste de Citrus aurantium et de Rosmarinus officinalis pour la lutte post-récolte contre les deux champignons de la tomate (Alternaria sp et Fusaruim sp) : étude in vitro et in vivo. - FERRAS, Douaa; BELAYACHI, Sennia (My University, 2025)
Tomato (Lycopersicon esculentum Mill.) is one of the most widely cultivated and consumed vegetables in the world. It is particularly vulnerable to fungal infections, especially those caused by Alternaria sp.and Fusarium oxysporum, which lead to significant losses in both yield and quality, in the field and during post-harvest storage. In this context, the present study evaluated the antifungal potential of essential oils extracted from rosemary (Rosmarinus officinalis) and bitter orange peel (Citrus aurantium), collected from two regions of Algeria: Mostaganem and Relizane. In vitro tests were conducted on the mycelial growth of Alternaria sp.and Fusarium oxysporum, while in vivo trials were carried out on post-harvest tomatoes using a combined formulation applied via three methods: passive diffusion, electric vaporization, and manual spraying. The in vitro results showed stronger antifungal activity from rosemary essential oil. Under in vivo conditions, the formulation effectively blocked the infection induced by Alternaria sp., with a protective effect persisting bey ond two weeks, particularly when applied using electric vaporization.These findings highlight the potential of essential oils as a natural alternative to chemical fungicides, for both crop protection and post-harvest fruit preservation.
Keywords: tomato, essential oils, rosemary, bitter orange, Alternaria sp., Fusarium oxysporum, post-harvest, biofungicide